1994
DOI: 10.1107/s0108767393013947
|View full text |Cite
|
Sign up to set email alerts
|

Thermal vibrations and bonding in GaAs: an extended-face crystal study

Abstract: Accurate X-ray integrated-intensity data collected from an extended-face crystal of GaAs are analysed to provide detailed information on the thermal vibrations of atomic species, including cubic anharmonicity, at room temperature. The values obtained for the thermal parameters are BGa = 0.622 (3) A 2, B s = 0.483(5)A 2 and ~GaAs'-" --0.6(1) X 10-18jX -3 (defined in the text). The inclusion of cubic anharmonic thermal vibrations is shown to be highly significant. In order to interpret the data collected for cer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 28 publications
(38 reference statements)
1
17
0
Order By: Relevance
“…This is explained by the constructive overlap of bonding orbitals and the charge transfer between nearest neighbours. As shown recently (Pietsch & Hansen, 1996), only a few of the charge density maps calculated from different data sets of X-ray structure amplitudes IFhl published until now (Levalois & Allais, 1986;Saravanan et aL, 1992;Stevenson, 1994) are in qualitative agreement with this theoretical prediction.…”
Section: Introductionmentioning
confidence: 73%
“…This is explained by the constructive overlap of bonding orbitals and the charge transfer between nearest neighbours. As shown recently (Pietsch & Hansen, 1996), only a few of the charge density maps calculated from different data sets of X-ray structure amplitudes IFhl published until now (Levalois & Allais, 1986;Saravanan et aL, 1992;Stevenson, 1994) are in qualitative agreement with this theoretical prediction.…”
Section: Introductionmentioning
confidence: 73%
“…Short discussions concerning the phase problem when using the Gram-Charlier expansion were published some years ago (Nelmes & Tun, 1987, 1988Hansen, 1988): the former authors showed that skewness can be detected by using a limited Gram-Charlier expansion, but that this is not the case for the Edgeworth expansion, whereas Hansen drew attention to the fact that the result is not unique. In a recent study of GaAs (Stevenson, 1994), there is also some discussion about poorly determined parameters (here third-order anharmonicity), which is explained by high correlations between these parameters.…”
Section: Introductionmentioning
confidence: 99%
“…There is no significant change in bond length between crystalline and amorphous samples, both of which agree with c-GaAs reference values. 25 The uncertainty in the bond length was approximately 60.009 Å . Compared with a crystalline coordination of four, the EXAFS analysis reveals a coordination of $2.8 for the amorphous samples.…”
Section: A the As Atom Environmentmentioning
confidence: 99%